6y= 2x + 8

What is the question?

Expert answered|yestfl|Points 104|

Question

Asked 11/13/2011 1:10:41 PM

Updated 4/14/2023 11:39:46 AM

1 Answer/Comment

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

Rating

3

6y= 2x + 8

dividing through by 2

y=1/3x+4/3.

Added 4/14/2023 11:39:46 AM

This answer has been confirmed as correct and helpful.

Simplify: 5(3x + 7) **Weegy:** 5(3x + 7)
= 15x + 35 (More)

Question

Expert Answered

Updated 7/8/2014 7:58:17 PM

0 Answers/Comments

Simplify: 6(a – 3b) + 2( -b – 4a) **Weegy:** 6(a-3b) + 2(-b -4a ) is equal to 6a-18b - 2b - 8a to simplify the answer is -2a - 16b = 2 ( -a + 8b). (More)

Question

Updated 7/8/2014 7:59:17 PM

2 Answers/Comments

6(a – 3b) + 2( -b – 4a)

= (6a - 18b) + (-8a - 2b)

= -2a - 20b

= (6a - 18b) + (-8a - 2b)

= -2a - 20b

Added 7/8/2014 7:59:17 PM

This answer has been confirmed as correct and helpful.

26 – 118 + 62 -2 =
**Weegy:** 26 – 118 + 62 -2 = -32
(More)

Question

Expert Answered

Asked 11/7/2011 6:40:13 AM

0 Answers/Comments

-35 – (-40) = **Weegy:**
-35 – (-40)
= -35 + 40
= 5
(More)

Question

Expert Answered

Updated 7/18/2020 6:19:02 PM

0 Answers/Comments

22(9×7) + 3 ×6 ÷ 2 +3(62 + 1)= **Weegy:** The result is 1584. (More)

Question

Expert Answered

Updated 294 days ago|11/28/2023 5:39:49 AM

1 Answer/Comment

22(9×7) + 3 ×6 ÷ 2 +3(62 + 1) =

Solution:

1. ( 9 × 7 = 63 )

2. ( 22 × 63 = 1386 )

3. ( 3 × 6 = 18 )

4. ( 18 ÷ 2 = 9 )

5. ( 62 + 1 = 63 )

6. ( 3 × 63 = 189 )

1386 + 9 + 189 =

The final answer is ( 1386 + 9 + 189 = 1584 ).

Solution:

1. ( 9 × 7 = 63 )

2. ( 22 × 63 = 1386 )

3. ( 3 × 6 = 18 )

4. ( 18 ÷ 2 = 9 )

5. ( 62 + 1 = 63 )

6. ( 3 × 63 = 189 )

1386 + 9 + 189 =

The final answer is ( 1386 + 9 + 189 = 1584 ).

Added 294 days ago|11/28/2023 5:39:49 AM

This answer has been confirmed as correct and helpful.

39,454,207

questions answered

There are no comments.